Y = -4/3x -1/2 , perpendicular slopes are opposite reciprocals
I believe the area of the blank rectangle, the biggest one, is 2800. The whole rectangle all together is 3225.
Explanation:
Since the length of one of the rectangles is 70, the rectangle with an area of 210 will have a side length of 3. This means the rectangle with an area of 15 has a side length of 5. <em>That</em> means the rectangle with an area of 200 has a side length of 40. Therefore, the blank rectangle has an area of 2800, as it's 2 side lengths are 70 and 40.
Answer:
prime
Step-by-step explanation:
x^2 + 10x – 18
What two numbers multiply to -18 and add to +10
There are no numbers that multiply to -18 and add to 10
-1 *18 = -18 -1 +18 = 17
-2 *9 = -18 -2 +9 = 7
This cannot be factored
Answer:
The function y = -x whose reflection in the line y =x is itself.
Step-by-step explanation:
A reflection that maps every point of a figure to an image across a fixed line. Then the fixed line is called the line of reflection.
The reflection of the point (x,y) in the line y = x is the point (y, x).
Therefore, the function y = -x whose reflection in the line y =x is itself.
Symmetries of the function f(x)= -x is:
A function symmetric with respect to the y-axis is called an even function.
If f(-x) = f(x)
A function that is symmetric with respect to the origin is called an odd function.
if f(-x) = -f(x)
then, we must look at f(-x);
f(x) = -x
f(-x)= -(-x)= x = -f(x)
this function is symmetrical to with respect to origin.
Therefore, this function is an odd function.
First, you need to rewrite the expression into binomial form, so you are working with two terms (as you world with a quadratic):
(x²)²-3(x²)-4=0
Now, you can place the x²s into brackets as the coefficient is now 1:
(x² )(x² )
Next, find out two numbers that add together to give you -3 and multiply to give -4 (these are the leftover integers after removing the x²s). These two numbers are -4 and 1.
Place the -4 and 1 into the brackets:
(x²-4)(x²+1)=0
Notice that the x²-4 is a difference of two squares, so can be further factorised into (x+2)(x-2)
This leaves you with a final factorisation of:
(x+2)(x-2)(x²+1)=0
Now we handle each bracket individually to obtain our four solutions for x:
x+2=0
x=-2
x-2=0
x=2
x²+1=0
x²=1
x=<span>±1</span>